Nonconvulsive status epilepticus as sign of tumor recurrence - Kae Nishiyama; Yuichi Kubota; Hidenori Ohbuchi; Suguru Yokosako; Shinji Hagiwara (Epilepsy & Behavior Reports, 2023)
Status epilepticus (SE) can be a sign of brain tumor progression or recurrence, but there are few reports of nonconvulsive status epilepticus (NCSE) being a sign of tumor progression or recurrence. Moreover, much remains to be elucidated about its clinical course, and outcome. This is the first report of NCSE associated with the progression of a metastatic brain tumor treated by surgical excision of the tumor. The patient was 74-year-old woman. She had a history of craniotomy for tumor resection and gamma knife treatment for multiple metastatic brain tumors originating from breast cancer. She suddenly developed dysarthria and right hemiparesis, followed by convulsive seizures in the right side of her body. Magnetic resonance imaging showed tumor recurrence in the left parietal lobe and worsening edematous changes around the tumor. Antiseizure medication was initiated, however her seizures did not improve; therefore, tumor resection was performed. Postoperatively, her consciousness, seizures, and electroencephalogram findings improved. NCSE caused by brain tumors may be refractory to treatment with antiseizure medications, and early surgical treatment may be useful for seizure control.